The Concept of Sirah Education Curriculum in Junior High School according to Abu Al-Hasan Ali Al-Nadwi - Mada Wijaya Kusumah; Tatang Hidayat; Abas Mansur Tamam; Ferli Septi Irwansyah (Islamic Research, 2023)
This article analyses the educational thought of Abu Al-Hasan Ali Al-Nadwi (d. 1999 A.D.). The study aimed to determine the concept of the Sirah education curriculum at the junior high school level, according to Abu Al-Hasan Ali Al-Nadwi. This type of research is categorized as library research, with data obtained from Al-Nadwi's books relating to Sirah and education in particular such as Al-Tarîq ilâ al-Madînah; Sîrah Khâtim al-Nabiyîn li al-Atfâl; Al-Sîrah Al-Nabawiyyah; Muslims in the West, Message, and Mission. The methods used in this study are descriptive research, qualitative research, and basic research. Based on the study results, two main thoughts about Sirah's education were found. First, the continuity of Sirah Education is essential, which means that Sirah education is taught for all generations. Furthermore, Sirah education means integrating Sirah education in subjects, especially religious aspects. The author's findings on the concept of the Sirah education curriculum at the junior high school level, according to Abu Al-Hasan Ali Al-Nadwi, are a set of objectives, programs, processes, and evaluations of Sirah education up to the junior high school level that can be given from class VII to grade IX junior high school. With the existence of Sirah Education, which aims to make the Prophet Muhammad Sallallahu 'Alaihi Wa Sallam an example for junior high school students, it is hoped that it can shape the Islamic personality of students at the junior high school level and give birth to Akhlaq al Karimah based on Tawhid.